War in Ukraine as a long-term effect of NATO intervention against Yugoslavia? An overview - Costamagna, Christian (Sociološki pregled, 2023)
The Russian invasion of Ukraine in February 2022 can also be traced back to historical processes and not only to contingent causes. In this paper, I will try to understand whether it is possible to argue that the current armed conflict in Ukraine is a long-term effect of the 1999 NATO bombing of Yugoslavia. The aim of the research is to critically analyze the interpretations that see in the NATO intervention against Yugoslavia a historical turning point and what consequences it had. The research is based on the current scholarly literature and on the speeches of Russian state officials, and is carried out adopting an historical approach and a comparative method.
Keywords: War in Ukraine; Russia; Operation Allied Force; West; Yugoslavia